The effect of guided imagery on physiological and psychological outcomes of adult ICU patients: A systematic literature review and methodological implications - Hadjibalassi, Maria; Lambrinou, Ekaterini; Papastavrou, Evridiki; Papathanassoglou, Elizabeth (My University, 2018)
Objectives: Guided imagery (GI) is a relaxation technique that is being increasingly explored in various patients’ populations. We systematically reviewed evidence on the effects of GI on physiological and psychological outcomes of adult critically ill patients and extracted implications for future research. Review method used: Systematic literature review of published studies based on the Cochrane Guidelines. Data sources: Studies were located through literature searches of CINAHL, PubMed, Embase, Cochrane Database of Systematic Reviews and Psych-Info. Review methods: We explored effects of GI in critically illness. The outcome measures included pain, anxiety, hemodynamic measurements, stress neuropeptides, length of stay, sleep quality, inflammatory markers, patient satisfaction and cost of care. The Cochrane Collaboration's tool for assessing risk of bias was employed. Extracted data included pathophysiological framework, sample, diagnoses of participants, specifics of intervention, design, experimental groups, analyses and main outcomes. Results: Based on the selection criteria, 10 studies were identified, involving N = 1391 critically ill patients. The main limitations include incomplete outcome data and selective reporting, incomplete blinding and lack of experimental group allocation concealment. Due to heterogeneity and incomplete reporting, a meta-analysis was not feasible. Our findings included: (a) favourable effects of the intervention with regard to decrease of pain, anxiety and LOS; (b) many studies employing randomised controlled trial designs; (c) a predominant focus on patients with cardiac surgery; (d) large heterogeneity in measurement of outcomes. Moreover, the evidence suggests that improvements in sleep quality, patient satisfaction and cost of care merit further investigation. Methodological implications include the need to clarify the underlying physiological framework, the use of repeated measure designs and the adjustment for confounders. Conclusions: On the basis of these results, and of the absence of reported side-effects, we conclude that GI is a promising patient-centered approach for the improvement of a number of patients’ outcomes that merits further investigation in critical care.
Keywords: Complementary alternative therapies; Critical illness; Guided imagery; Relaxation; Systematic review